2005
DOI: 10.4153/cjm-2005-027-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of the Spreading Models of a Banach Space

Abstract: Abstract. We study some questions concerning the structure of the set of spreading models of a separable infinite-dimensional Banach space X. In particular we give an example of a reflexive X so that all spreading models of X contain ℓ 1 but none of them is isomorphic to ℓ 1 . We also prove that for any countable set C of spreading models generated by weakly null sequences there is a spreading model generated by a weakly null sequence which dominates each element of C. In certain cases this ensures that X admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 25 publications
(69 reference statements)
0
50
0
Order By: Relevance
“…COLUMN 2: Apply Remark 2.6 to (y (2,2)} to obtain a subarray (y 2 i,j ) (i,j)∈I with the property that for all a in A,…”
Section: Extension Of Odell's Schreier Unconditionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…COLUMN 2: Apply Remark 2.6 to (y (2,2)} to obtain a subarray (y 2 i,j ) (i,j)∈I with the property that for all a in A,…”
Section: Extension Of Odell's Schreier Unconditionalitymentioning
confidence: 99%
“…Therefore for the "multiple of the inclusion plus compact problem" we only examine HI saturated Banach spaces. In Section 3 we prove Theorems 3.2 and 3.8 which give sufficient conditions on a Banach space X so that the "multiple of the inclusion plus compact" problem to have an affirmative answer in X, and extend results of [2] and [21]. In his 2000 dissertation N. Dew [7] introduced a new HI space which we refer to as space D. In Section 4 we examine some of the basic properties of D and we apply Theorem 3.8 to prove that the"multiple of the inclusion plus compact" problem has an affirmative answer in D.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [4], it was shown that there exist hereditarily indecomposable spaces not admitting any ℓ p or c 0 as a spreading model. In [1], the authors construct a space not admitting an ℓ p , c 0 or reflexive spreading model. In paper [3] they show that a variant of the space X S does not admit any ℓ p or c 0 as a k-iterated spreading model for any k ∈ N.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes knowledge of the spreading models can be used to deduce subspace knowledge about X itself (e.g., [AOST,OS1]) but the relationship is still not completely understood. Spaces with no "nice" subspaces can have very nice spreading models (e.g., [AD]).…”
Section: Introductionmentioning
confidence: 99%